Kewajiban Belajar - Zulfahmi Lubis (UIN Sumatera Utara Medan, 2016)
Abstrak: Islam has obligated his followers to learn either is man or woman. The Instrucition for learning and education obtains for long live and for the farest district such as China. Some hadis talked obut it are weak according to its sanad but just because many sanad talked about it than it becomes good.According to Islamic tought that sciences drived into two kinds; fardhu `ain and fardhu kifayah. Fardhu `ain related to the religious sciences and fardhu kifayah related to every science that has usefull for human civilizations. Islam repects the sciences and the scholars and honors them among the creatures.